Igf2 Gene Expression Levels in Wild-Type and Mutant Mice - Tran, Giang Van; Tran, Dung Quoc; Thanh, Pham; Ty, Nguyen; Chinh, Pham Quang (Open Science Journal, 2017)
Genomic imprinting occurs where only one allele of a gene is expressed depending on its parental origin. The imprinted Igf2 gene (Insulin-like growth factor 2) is encoding a growth factor, which play an important role in embryonic development and formation of the placenta. The regulation and expression of Igf2 is carried out by different promoters. Promoter expression is extremely complex in wild-type mice during development and is altered in several mutant mice bearing deletions at the Igf2/H19 locus. In this work, we analyzed the Igf2 RNA expression of the placenta-specific P0 promoter in placental tissue (embryonic day 17) of both wild-type and mutant mice. For all the other promoters, we used RNA extracted from liver tissues (postnatal day 7.5). All these RNAs were reverse transcribed to cDNA before quantifying expression levels of the promoters by quantitative PCR (qPCR).Our results show that transcriptions of Igf2 P2 and P3 promoters are the highest in all mice analyzed, except in ΔU2/Dom mutant mice where P0 and P1 promoters were highly expressed, while they display low expression in all the other mice strains analyzed. Furthermore, all promoters were stably expressed at high levels in wild-type and ΔU2/Dom mutation, but at a low level in Δ3/Dom